Transcripción y adaptación para voz y piano de géneros tradicionales ecuatorianos y latinoamericanos del cantautor Filemón Arquímedes Macías Joza - Salmerón Brito, Brigith Antonella (2024)
The artistic product entitled Transcription and adaptation for voice and piano of traditional Ecuadorian and Latin-American genres from the singer-songwriter Filemon Arquimedes Macias Joza, states as objective to contribute to the preservation and diffusion of Latin-American and mixed Ecuadorian traditional music, with a special focus in the music scene of the Manabi Province. These genres represent a great part of our cultural identity as Ecuadorians and even more, represent a valuable heritage that must be transmitted from generation to generation. The presented theorical study addresses fundamental aspects of Latin- American and Ecuadorian music, the transcription and musical adaptation, the lied form for piano and vocals, and a brief biography of Filemon Macias. Through several processes that combine documental investigation, interviews, registry files, transcription and adaptation of selected works from the repertoire of the aforementioned Manabitan singer-songwriter, the aim was to highlight and promote the musical and cultural identity of his repertoire, as it was aimed that the Manabi-music transcends borders and reaches a broader public, in both national and international level. As a result of this artistic product, it was possible to adapt to piano and vocal format, seven works correspondents with traditional Ecuadorian and Latin-American genres from the singer-songwriter Filemon Arquimedes Macias Joza. Said adaptation is found in a music score brochure called Manabitan harmonies: the musical legacy of Dr. Filemon Macias, which contains the scores adapted for the before mentioned format and its correspondent lyrics. Finally, is recommended the use of several platforms and mediums to preserve Manabi music, including concerts, lectures and collaborations with media platforms with means of divulge the artistic legacy to national and international levels Keywords: Musical transcription, vocal and instrumental genres, latin American music, Filemón Arquimedes Macías Joza